Optimalisasi Tensi Keliling untuk deteksi dini Hipertensi di Desa Sanahu - Ronald Darlly Hukubun; Michael Hemsly Munda; Lusty Inggina Makatita; Christofel Elia Rahakbauw; Freadly C. Wenno; Laura Bianca Sylvia Huwae (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Hypertension is a highly prevalent non-communicable disease often referred to as "The Silent Killer" because it rarely shows symptoms until it causes serious complications such as stroke, kidney failure, and heart disease. This community service activity aims to optimize the Mobile Blood Pressure Monitoring Program as a hypertension screening method in Sanahu Village. The methods used include participant data collection, blood pressure checks with a manual sphygmomanometer, and health education on hypertension prevention. A total of 96 participants participated in this activity, and the results showed that 58 participants (60.4%) were hypertensive. This program has proven effective in reaching communities with limited access to health services and raising public awareness about the importance of early detection of non-communicable diseases. In addition, this activity succeeded in providing knowledge to the community about how to prevent hypertension and the importance of maintaining a healthy lifestyle, which is expected to reduce the incidence of hypertension in the future.